Desert Mementos : Stories of Iraq and Nevada - Cage, Caleb S., 1979- (Book collections on Project MUSE., 2017)
"Desert Mementos capture the similarities in the respective desert landscapes of both Iraq and Nevada. But it is not just a study in contrasting landscapes. Desert Mementos explores the similarities and differences in human needs from the perspectives of vastly different cultures and in vastly different environments."--Provided by publisher.